UPACARA ROKAT DALAM TRADISI MADURA: TINJAUAN LIVING HADIST - Badrud Tamam (Khazanah: Jurnal Sejarah dan Kebudayaan Islam, 2021)
Islam is a religion with the universe spirit, that made it lives and thrives in diverse society. When Islam developed outside of Arabia, it came into contact with other culture. In its interaction between Islam and other culture, creating a harmonization of islamic values with local cultures values. In the islamic scholarship this is known as the living hadist. One of the example is upacara rokat in the Madurese culture who has experienced Islamization. Origanlly, the upacara rokat came from a pre-islamic traditions.